Optimal severance pay in a matching model - Giulio Fella (Queen Mary University of London, Department of Economics, 2007)
This paper uses an equilibrium matching framework to study jointly the optimal private provision of severance pay and the allocational and welfare consequences of government intervention in excess of private arrangements. Firms insure risk-averse workers by means of simple explicit employment contracts. Contracts can be renegotiated ex post by mutual consent. It is shown that the privately optimal severance payment is bounded below by the fall in lifetime wealth associated with job loss. Simulations show that, despite contract incompleteness, legislated dismissal costs largely in excess of such private optimum are effectively undone by renegotiation and have only a small allocational effect. Welfare falls. Yet, for deviations from laissez faire in line with those observed for most OECD countries, the welfare loss is small.
Keywords: J23; J64; J65; 330; Severance pay; Contracts; Renegotiation; Abfindung; Mathematische Optimierung; Allgemeines Gleichgewicht; Vertragstheorie